On Why A Single Legal Test Should Cover the Entire Sphere of Exploitative Abuse in EU Competition Law - Kunnari, Antti (My University, 2020)
Exploitative abuse in the context of the TFEU article 102 (a) includes three types of behavior: unfairly high and unfairly low pricing, as well as other unfair trading conditions. The first two behaviors occur when a dominant firm can leverage its market power in such a way that it can sell its outputs at too high a price or buy inputs at too low a price to or from a trading partner. The third type of behavior involves a dominant firm imposing overly onerous, non-price related conditions to the detriment of such partner. We argue that all of these conducts are in fact very similar to each other and making a distinction between them is unnecessary when testing if a conduct constitutes an abuse. This similarity stems from the finding that high and low pricing are both different sides of the same coin, and it is only the direction of the unfairness that changes. Non-price related onerous trading conditions in turn are in fact instances of either high or low pricing, depending on whether the abuser is the seller or the buyer. One cannot dissociate the non-price related trading conditions from pricing, as they together form the transaction. Onerous trading conditions might not be considered onerous if the abuser is ready to pay more for imposing those conditions when it is the buyer. If it is the seller, onerous conditions imposed might not be unfair should the abuser be willing to lower the price. One cannot find abuse either by examining prices, as the accompanying conditions might be surprisingly stringent or lenient. Unfairly high pricing is tested on a standard established by the Court of Justice in United Brands. It requires that one must look at if the abuser’s profit margin is excessive, if price seems unfair when compared to, for example, its competitors’ prices and if the price is unfair when compared to a simulated competitive situation. There is no established test for low pricing. The Court has found that for a non-price related condition not to constitute an abuse, it must be necessary and proportionate. Because, inter alia, all three types of exploitation are economically similar, because the United Brands test has the potential to be responsive in all three types of exploitation, and because the necessity and proportionality test in fact measures the same thing as United Brands, we come to the conclusion that the United Brands test should be used in response to all types of suspected exploitative abuse. The European Commission and the national authorities have rediscovered exploitation in their enforcement toolboxes to address the complexity of the platforms. Furthermore, the COVID-19 crisis has demonstrated that competition law could have some tools to address possibly immoral price gouging. The topic is systemically important, because if one test does not cover all the types of exploitation which are in fact similar, there is a risk that the finding of abuse depends on the choice of test and not on the facts, which is unacceptable for any legal system.

SEUT 102 (a) artiklan tarkoittama markkinavoiman hyväksikäyttöön perustuva väärinkäyttö sisältää kolmen tyypistä toimintaa: yli- ja alihinnoittelua sekä muita kohtuuttomia kauppaehtoja. Kaksi ensimmäistä merkitsee sitä, että yritys kykenee markkinavoimaansa hyödyntäen myymään ylihinnalla tai ostamaan alihinnalla hyödykkeitä suhteessa kauppakumppaniinsa. Kolmas tarkoittaa väärinkäyttäjän vaativan liian ankaria hintaan suorasti liittymättömiä ehtoja. Väitämme, että tosiasiallisesti kaikki edellä mainitut väärinkäytön tyypit ovat pohjimmiltaan niin samankaltaisia, että erottelu on tarpeetonta. Yli- ja alihinnoittelu ovat todellisuudessa vain saman kolikon kaksi puolta, sillä ainoastaan kohtuuttomuuden suunta vaihtuu. Hintaan liittymättömät kohtuuttomat kauppaehdot puolestaan ovat todellisuudessa joko yli- tai alihinnoitte-lua riippuen siitä, onko väärinkäyttäjä osapuolena ostajana vai myyjänä. On mahdotonta irrottaa muita kohtuuttomia kauppaehtoja hinnoista, sillä ne yhdessä muodostavat kauppasuhteen keskeisen sisällön. Jos väärinkäyttäjä on suhteessa ostajana/myyjänä, sen määräämät kohtuuttomat ehdot eivät ole välttämättä kohtuuttomia, jos se on valmis maksamaan korvausta / tarjoamaan alempaa hintaa myyjälle/ostajalle hyödykkeestä. Ei ole toisaalta hyväksyttävää löytää kohtuuttomuutta vain tarkastelemalla hintoja, sillä muut ehdot voivat muuttaa kohtuullisuusarviointia. EUT on kehittänyt Asiassa United Brands testin ylihinnoittelun toteamiseksi. Ylihinnoittelu voidaan löytää tarkastelemalla väärinkäyttäjän kannattavuutta, vertaamalla hintoja esimerkiksi kilpailijoiden hintoihin ja tarkastelemalla onko hintataso kohtuullinen suhteessa kuvitteelliseen kilpailulliseen tilanteeseen. Alihinnoitteluun ei ole testiä. Muiden kohtuuttomien kauppaehtojen osalta EUT on vaatinut ehdon tarpeellisuutta ja oikeasuhtaisuutta. Koska muun muassa tarkasteltavat väärinkäytön muodot ovat riittävän samankaltaisia, koska United Brands testi on responsiivinen huolimatta väärinkäytön ilmenemistavasta ja koska tarpeellisuuden ja oikeasuhtaisuuden tarkastelu tosiasiassa testaa samaa asiaa kuin United Brands, tulemme siihen lopputulokseen, että kyseistä testiä tulisi käyttää riippumatta väärinkäytön muodosta. Komissio ja erityisesti kansalliset viranomaiset ovat jälleen kaivaneet työkalupakistaan markkinavoiman hyväksikäyttöön perustuvan väärinkäytön suitsiakseen alustatalouden monimutkaisia liiketoimintamalleja. Lisäksi se on nostanut päätään koronakriisissä, sillä kriisi on nostanut joidenkin hyödykkeiden hintoja rajusti. Oikeussystemaattisesti aihe on myös tärkeä, sillä olisi kestämätöntä, jos todellisuudessa samanlaisia käyttäytymisen väärinkäytön muotoja ei testata yhdenmukaisesti, mikä voisi johtaa epäjohdonmukaisuuteen ratkaisutoiminnassa.
Keywords: Exploitative abuse, exploitation, excessive pricing, unfairly high pricing, unfairly low pricing, other onerous trading conditions, TFEU article 102 (a), United Brands Case 27/76, economic value, legal test, buyer power, platform enforcement